Changing the model of radiography practice: Challenges of role advancement and future needs for radiographers working in the UAE. Issue 4 (November 2022) - Elshami, W.; Abuzaid, M.M.; McConnell, J.; Baird, M.
Abstract: Introduction: The radiographers' role in the United Arab Emirates (UAE) is focused on image acquisition with a willingness to accept advanced practice roles after appropriate education and training. Radiographers working in the UAE are highly motivated and ambitious to achieve those internationally identified levels of professional recognition and opportunities for role advancement. This study investigates the radiographers' perspectives, perceptions and hopes for role advancement in the UAE. Methods: A qualitative research study design using Focus Group Discussions (FGD) was used to elicit the perceptions of radiographers. Participants were radiographers working in the hospitals and clinics supervised by the Ministry of Health and Prevention. Participants were asked about the recognized tasks defined as advancement roles, needs for roles clinically, challenges and requirements to prepare radiographers to participate in extended/developed roles. The discussions were audio recorded and later transcribed by an independent research assistant. Thematic analysis was used for data analysis Results: 29 radiographers participated in the FGDs, and 83% (n = 24) were interested in role advancement. FGD revealed that their current practice showed some informal extended role that may promote career progression. The most significant challenges identified by participants was their knowledge level as provided by the current curriculum and the need for education and licensing body support to accommodate change. Conclusion: The study identified a need for education and licensing body support to enable change in roles by radiographers, through improving radiographer knowledge and experience for role advancement. Implications for practice: To sustain role advancement, formal intense training and education are necessary, normally above bachelor's degree level. Furthermore, establishing standards, licensing organizations/professional bodies should be part of the transformation of the profession to enable internationally recognized models to be followed.